Curriculum Reform: A Transformation of Educational Progress - Ishak, Musli; Yahiji, Kasim; Manopo, Yanti K,; Arsyad, Lukman (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
Curriculum renewal is a strategic agenda in responding to the challenges of globalization, technological developments, and the demands of 21st century competencies. This article discusses the urgency of curriculum transformation in Indonesian education with a focus on the implementation of the Independent Curriculum as an effort to improve the quality and relevance of learning. The main objective of this study is to explore the dynamics of curriculum renewal implementation in various geographical contexts and identify the determinants of its success. This study uses a qualitative approach with a multi-site case study type. Data were collected through in-depth interviews, observations, and documentation from 15 informants in urban, semi-urban, and rural areas, then analyzed thematically. The results of the study indicate a significant implementation gap between regions, influenced by teacher readiness, institutional support, and infrastructure. These findings enrich the understanding of the importance of a contextual approach and policy differentiation in curriculum implementation. In conclusion, curriculum renewal will only be effective if supported by adaptive policies, ongoing training, and equal access to educational technology. Further research is recommended to use a longitudinal approach and data triangulation to deepen understanding of the process of sustainable educational transformation.